Method for preparing high-filling low-modulus stretchable thermal interface material based on physical loose entanglement
By introducing free macromolecules and free small molecules into the polymer matrix, adjusting the physical entanglement and cross-linking situation, and using multi-scale composite thermal conductivity particle ratios, a thermal interface material with high filling amount and low modulus and high ductility is prepared, solving the problem of difficult to take into account both thermal conductivity and flexibility in the prior art, and achieving efficient heat dissipation of electronic equipment.
Patent Information
- Application Number
- CN202510145918.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-10
AI Technical Summary
When existing thermal interface materials pursue high thermal conductivity, it is difficult to take into account low modulus and high ductility, resulting in a contradiction between flexibility and thermal conductivity in the heat dissipation application of electronic equipment.
By introducing free macromolecular segments and free small molecules into the polymer matrix, the physical entanglement and cross-linking situation is adjusted, and the thermal interface materials with high fill amount and low modulus and high ductility are prepared.
It realizes the soft and tensile characteristics of the thermal interface material with high thermal conductivity particle filling amount, which meets the heat dissipation needs of electronic equipment.
Smart Images

Figure CN119842041A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of thermal interface heat-conducting materials, and in particular relates to a method for preparing a high-filling, low-modulus stretchable thermal interface material based on physical loose entanglement. Background Art
[0002] Typically, thermal interface material is an elastomer composite material consisting of an elastomer matrix and thermally conductive particles, and is used to fill between a heat sink and a heat-generating device to reduce contact thermal resistance.
[0003] In order to ensure the normal operation of the heating element, the thermal interface material used is required to have high thermal conductivity to meet the need to quickly transfer heat from the heating element to the heat sink.
[0004] However, in the actual application scenarios of thermal interface materials, during the heating and cooling process of the chip, the thermal interface material will produce thermal stress and deformation due to the different material expansion coefficients. In order to avoid the uneven surface of the chip and the heat sink, rigid contact leaving thermal insulation gaps, etc., the thermal interface has low modulus and high ductility.
[0005] In order to pursue higher thermal conductivity, researchers often add ultra-high content of thermal conductive fillers to the elastomer matrix to form a thermal conductive path between the particles, thereby improving the thermal conductivity of the thermal interface material. Studies have shown that the thermal conductivity of thermal interface materials increases exponentially with the amount of thermal conductive particles filled, that is, the more fillers are added, the higher the filler density per unit volume, the thermal conductivity increases exponentially, and the contact thermal resistance is greatly reduced. Therefore, in order to achieve higher thermal conductivity, thermal interface materials usually need to be filled with ultra-high content of thermal conductive particles to achieve higher thermal conductivity, but the increase in fillers will inevitably lead to an increase in the Young's modulus of the material. Therefore, high thermal conductivity and good flexibility are generally not available at the same time, but in order to meet the increasingly diverse heat dissipation requirements of today's electronic devices, a balance must be found between the flexibility and thermal conductivity of thermal interface materials. Therefore, the coexistence of seemingly contradictory properties between low modulus and high ductility and high thermal conductivity particle filling is still a continuous challenge facing existing thermal interface materials.
[0006] In previous studies, it has been proven that in thermal interface materials, although the content of polymer matrix is very low, it plays a decisive role in the mechanical properties of composite materials. Studies have shown that the entanglement in the polymer plays the role of a slip chain, which can transfer the force along the chain to many other chains. Through the synergistic effect of crosslinking and entanglement, the good elasticity and stretchability of the elastomer can be achieved. Therefore, how to control the appropriate degree of physical entanglement in thermal interface materials to ensure the excellent stretchability of thermal interface materials is undoubtedly a very promising direction. Summary of the invention
[0007] The purpose of the present invention is to solve the contradiction between low modulus high ductility and high thermal conductive particle filling, and to provide a method for preparing a high-filled low modulus stretchable thermal interface material based on physical loose entanglement.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a high-filled, low-modulus stretchable thermal interface material based on physical loose entanglement, the method comprising:
[0010] Step 1: dissolving isophorone diisocyanate in an organic solvent to obtain solution A; dissolving polytetrahydrofuran-2000 in an organic solvent to obtain solution B; dissolving hydroxyethyl acrylate in an organic solvent to obtain solution C; under a nitrogen atmosphere, heating at 75°C with magnetic stirring, adding solution A dropwise to solution B within 10 minutes, and reacting for 4 hours, during which the hydroxyl group in the diol (polytetrahydrofuran-2000) reacts with the isocyanate functional group of the diisocyanate (isophorone diisocyanate) to produce to form an isocyanate-terminated polyurethane prepolymer; under a nitrogen atmosphere, heat at 75°C with magnetic stirring, and dropwise add solution C to the above solution within 10 minutes to react for 2 hours; during this process, the hydroxyl group in hydroxyethyl acrylate will react with the isocyanate functional group in the prepolymer to terminate the prepolymer, and the reaction will obtain acrylate-terminated polyurethane acrylate; the organic solvent plays a role in reducing viscosity and preventing violent reactions due to excessive concentration, and does not participate in the reaction, so there is no requirement for the concentrations of solution A, solution B, and solution C;
[0011] Step 2: pour out the reaction solution obtained in step 1, dry it in a vacuum oven at 80°C for 24 hours, and then dry it in a blast drying oven at 80°C for 24 hours to obtain polyurethane acrylate PUA; the two-step drying is to remove the solvent completely;
[0012] Step 3: Weigh 10g polyurethane acrylate (PUA), 1.21-3.63g hydroxyethyl acrylate (HEA), 2.136-5.20g tetrakis (3-mercaptopropionic acid) pentaerythritol ester (PETMP), add 13.35-18.83g of polypropylene glycol 400 (PPG-400) and polypropylene glycol 3000 (PPG3000) mixture, then add 106.8-150.64g spherical alumina thermal conductive particles, mix well, add 0.03g catalyst, pour into the mold and stand at room temperature for curing. Step 1 synthesizes the polymer main chain, on this basis, the hydroxyethyl acrylate in step 3 forms a pendant side chain, and PETMP is a tetrafunctional thiol curing agent that undergoes a thiol-ene click reaction with a double bond.
[0013] Furthermore, in step 1, the organic solvent is one or more of tetrahydrofuran (THF), dioxane, pyridine, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0014] Furthermore, in step 1, the molar ratio of isophorone diisocyanate, polytetramethylene furan-2000 and hydroxyethyl acrylate is 20:10:20.
[0015] Furthermore, in step three, the mass ratio of polypropylene glycol 3000 (PPG3000) to polypropylene glycol 400 (PPG-400) is 3:0-3.
[0016] Furthermore, in step three, among the spherical alumina thermally conductive particles, 50 μm spherical alumina accounts for 52.5 wt %, 20 μm spherical alumina accounts for 13.5 wt %, and 10 μm spherical alumina accounts for 34 wt %.
[0017] Furthermore, in step three, the catalyst is one or more of 1,8-diazabicyclo[5.4.0]undec-7-ene DBU, triethylamine, tetramethylguanidine, hexahydropyridine, tetrahydropyridine, and triethylenediamine.
[0018] The beneficial effects of the present invention compared to the prior art are:
[0019] (1) The present invention uses small-sized particles to fill the gaps between large-sized particles while ensuring the same filler content, so that the fillers are stacked more densely, thereby reducing the thermal resistance between the fillers and improving the thermal conductivity of the thermal interface material.
[0020] (2) By introducing free macromolecular segments and free small molecules into the polymer matrix, the physical entanglement and crosslinking of the thermal interface material are adjusted. The stretchability and elasticity are achieved by lengthening the free polymer chains to form appropriate entanglements, where loose entanglements transfer the applied force to a large area and hard crosslinks prevent the entanglement from unravelling. That is, the ratio of two internal dispersion media with different molecular weights, polypropylene glycol 400 and polypropylene glycol 3000, in the thermal interface material is adjusted to achieve loose physical entanglement, solve the problem of the compliance of the thermal interface material under high thermal conductive particle filling, and thus achieve the coupling relationship between high filling amount and low modulus and high ductility.
[0021] (3) The present invention introduces internal dispersion media of different molecular weights into the thermal interface material to adjust the physical cross-linking and entanglement of the thermal interface material, thereby preparing a soft and stretchable thermal interface material that has both high thermal conductive particle filling and low modulus compliance and ductility. The thermal interface material finally prepared achieves a high elongation at break of 694% and a low Young's modulus of 72.6 kPa under a high load of 80% alumina. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the synthesis scheme of the polymer main chain;
[0023] Figure 2 This is the Fourier infrared test data result diagram of the polymer main chain before and after curing;
[0024] Figure 3 is the particle size distribution diagram of spherical alumina with different particle sizes;
[0025] Figure 4 It is the tensile curve diagram of the thermal interface material obtained with different mass ratios of polypropylene glycol 3000 / polypropylene glycol 400;
[0026] Figure 5 This is a comparison chart of the tensile modulus of thermal interface materials obtained with different mass ratios of polypropylene glycol 3000 / polypropylene glycol 400;
[0027] Figure 6 It is a fitting analysis diagram of chemical crosslinking modulus and physical entanglement modulus when the mass ratio of polypropylene glycol 3000 / polypropylene glycol 400 is 1:0;
[0028] Figure 7 It is a fitting analysis diagram of chemical crosslinking modulus and physical entanglement modulus when the mass ratio of polypropylene glycol 3000 / polypropylene glycol 400 is 3:1;
[0029] Figure 8 It is a fitting analysis diagram of chemical crosslinking modulus and physical entanglement modulus when the mass ratio of polypropylene glycol 3000 / polypropylene glycol 400 is 1:1;
[0030] Fig. 9 This is a comparison chart of chemical crosslinking modulus and physical entanglement modulus at different mass ratios of polypropylene glycol 3000 / polypropylene glycol 400;
[0031] Fig.10 This is the effect picture of thermal interface material used for heat dissipation of 1W LED small lamp beads;
[0032] Fig.11 Schematic diagram of the loose entanglement mechanism of the polymer network of thermal interface materials. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0034] Compounding of thermally conductive particles: Considering that thermally conductive fillers with smaller particle sizes will improve toughness but show weaker thermal conductivity, and thermally conductive fillers with larger particle sizes will damage toughness but show higher thermal conductivity, three spherical alumina powders with different particle sizes were selected, and their particle size distribution was characterized by a laser powder size analyzer, such as Figure 3 As shown in the figure, the particle size distribution of the three different particle sizes of alumina powder is unimodal, and the main particle size distribution does not overlap. The particle size distribution is calculated by the Dinger-Funk equation to obtain the best ratio of the three different particle sizes, where 50μm spherical alumina accounts for 52.5wt%, 20μm spherical alumina accounts for 13.5wt%, and 10μm spherical alumina accounts for 34wt%. Under this particle size distribution, the three particles are closely arranged, which can achieve the closest arrangement to achieve a better thermal conductivity path.
[0035] Embodiment 1:
[0036] Synthesis of polymer backbone polyurethane acrylate (PUA): Synthesis route such as Figure 1 First, weigh 20 mmol of isophorone diisocyanate and dissolve it in 80 ml of N, N-dimethylformamide. Heat and magnetically stir at 75°C under a nitrogen atmosphere. Add 10 mmol of polytetrahydrofuran ether diol dissolved in 20 ml of N, N-dimethylformamide dropwise within 10 minutes and react for 4 hours. Then, under a nitrogen atmosphere, heat and magnetically stir at 75°C and add 20 mmol of hydroxyethyl acrylate dissolved in 20 ml of N, N-dimethylformamide dropwise within 10 minutes and react for 2 hours.
[0037] Post-treatment scheme: pour out the reaction solution, dry it in a vacuum oven at 80° C. for 24 h, and then dry it in a forced air drying oven at 80° C. for 24 h to obtain the product polyurethane acrylate PUA.
[0038] Preparation of multi-scale composite thermal conductive particles: Take 52.5 g of 50 μm spherical alumina, 13.5 g of 20 μm spherical alumina, and 34 g of 10 μm spherical alumina, mix them thoroughly and evenly to obtain multi-scale composite spherical alumina powder.
[0039] Preparation of thermal interface material: weigh 10g PUA, 2.66g hydroxyethyl acrylate, 3.98g pentaerythritol tetrakis(3-mercaptopropionic acid) ester, add 16.64g polypropylene glycol 3000, then weigh 80% of the total mass of the system multi-scale composite thermal conductive particles, mix well, add 0.03g catalyst DBU, pour into a silicone mold and let stand at room temperature to cure.
[0040] The prepared thermal interface material was subjected to mechanical tensile tests, such as Figure 4 As shown, Figure 4The obtained data is used to calculate the tensile modulus as Figure 5 As shown, Figure 4 The obtained data are fitted and calculated, such as Figure 6 As shown, the physical entanglement modulus / chemical crosslinking modulus is obtained, such as Fig. 9 As shown in the figure, the analysis shows that when the ratio of free macromolecules to free small molecules is 3:0, that is, only relying on the hard physical entanglement brought by the free macromolecules, the prepared thermal interface material has a larger tensile modulus and a lower elongation at break.
[0041] Through Fourier infrared test, such as Figure 2 As shown in the infrared spectrum, no peak at 2200 cm -1 The characteristic absorption peak of isocyanate at 3300 cm -1 A new absorption peak appeared near 1640cm -1 The disappearance of the absorption peak near indicates that the carbon-carbon double bond has reacted successfully.
[0042] Embodiment 2:
[0043] The difference between this embodiment and embodiment 1 is that the polypropylene glycol 3000 added in embodiment 1 is replaced by a mixture of polypropylene glycol 3000 and polypropylene glycol 400, the total mass remains unchanged, and the mass ratio of polypropylene glycol 3000 to polypropylene glycol 400 is 3:1.
[0044] The prepared thermal interface material was subjected to mechanical tensile tests, such as Figure 4 As shown, Figure 4 The tensile modulus is calculated by the obtained data. Figure 5 As shown, Figure 4 The obtained data are fitted and calculated, such as Figure 7 As shown, the physical entanglement modulus / chemical crosslinking modulus is obtained, such as Fig. 9 As shown, analysis shows that compared with Experimental Example 1, Experimental Example 2 introduces a non-reactive free small molecule dispersion medium on the basis of the hard physical entanglement brought by the free macromolecule alone, reduces the adverse effects of the hard physical entanglement on the tensile properties, improves the fluidity of the polymer chain, improves the tensile properties, reduces the physical entanglement modulus of the thermal interface material, and the chemical crosslinking modulus remains basically unchanged. Among them, polypropylene glycol 3000 is a free macromolecule and polypropylene glycol 400 is a free small molecule. The two create a loose physical entanglement to facilitate the chain segment slippage during the material stretching process. Its mechanism of action is as follows Fig.11 shown.
[0045] Embodiment 3:
[0046] The difference between this embodiment and embodiment 1 is that the polypropylene glycol 3000 added in embodiment 1 is replaced by a mixture of polypropylene glycol 3000 and polypropylene glycol 400, the total mass remains unchanged, and the mass ratio of polypropylene glycol 3000 to polypropylene glycol 400 is 1:1.
[0047] The prepared thermal interface material is subjected to mechanical tensile test to obtain the stress-strain curve, such as Figure 4 As shown, Figure 4 The obtained data is used to calculate the tensile modulus as Figure 5 As shown, Figure 4 The obtained data are fitted and calculated, such as Figure 8 As shown, the physical entanglement modulus / chemical crosslinking modulus is obtained, such as Fig. 9 As shown. Analysis shows that, compared with Experimental Example 2, Experimental Example 3 introduces more non-reactive free small molecule dispersion medium, significantly reducing the adverse effects of hard physical entanglement on tensile properties, creating loose physical entanglement, so that the chain segments slip during material stretching, improving the fluidity of the polymer chain, and significantly improving the tensile properties. The elongation at break is increased by two times compared with Example 1, the tensile modulus and physical entanglement modulus are significantly reduced, while the chemical crosslinking modulus remains basically unchanged, meeting the requirements of high filling and low modulus stretchability.
[0048] The prepared thermal interface material was used for heat dissipation test of 1W LED lamp beads. Fig.10 As shown, through the comparison with no thermal interface material, it can be analyzed that the prepared thermal interface material has excellent heat dissipation capability.
Claims
1. A method for preparing a highly filled low modulus stretchable thermal interface material based on physical loose entanglement, characterized in that: The method is: Step 1: dissolving isophorone diisocyanate in an organic solvent to obtain solution A; dissolving polytetrahydrofuran-2000 in an organic solvent to obtain solution B; dissolving hydroxyethyl acrylate in an organic solvent to obtain solution C; Under a nitrogen atmosphere, heat at 75°C with magnetic stirring, add solution A dropwise to solution B within 10 min, and react for 4 h. Under a nitrogen atmosphere, heat at 75°C with magnetic stirring, add solution C dropwise to the above solution within 10 min, and react for 2 h. Step 2: pour out the reaction solution obtained in step 1, dry it in a vacuum oven at 80° C. for 24 hours, and then dry it in a forced air drying oven at 80° C. for 24 hours to obtain polyurethane acrylate; Step 3: Weigh 10g of polyurethane acrylate, 1.21-3.63g of hydroxyethyl acrylate, 2.136-5.20g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester, add 13.35-18.83g of a mixture of polypropylene glycol 400 (PPG-400) and polypropylene glycol 3000 (PPG3000), then add 106.8-150.64g of spherical alumina thermal conductive particles, mix well, add 0.03g of catalyst, pour into a mold and let stand at room temperature to cure.
2. A method for preparing a high-filled low-modulus stretchable thermal interface material based on physical loose entanglement according to claim 1, characterized in that: In step 1, the organic solvent is one or more of tetrahydrofuran, dioxane, pyridine, N,N-dimethylformamide, and N,N-dimethylacetamide.
3. The method for preparing a high-filling, low-modulus stretchable thermal interface material based on physical loose entanglement according to claim 1, characterized in that: In step 1, the molar ratio of isophorone diisocyanate, polytetramethylene furan-2000 and hydroxyethyl acrylate is 20:10:
20.
4. The method for preparing a high-filled low-modulus stretchable thermal interface material based on physical loose entanglement according to claim 1, characterized in that: In step 3, the mass ratio of polypropylene glycol 3000 (PPG3000) to polypropylene glycol 400 (PPG-400) is 3:0-3.
5. The method for preparing a high-filling, low-modulus stretchable thermal interface material based on physical loose entanglement according to claim 1, characterized in that: In step three, among the spherical alumina thermal conductive particles, 50 μm spherical alumina accounts for 52.5 wt %, 20 μm spherical alumina accounts for 13.5 wt %, and 10 μm spherical alumina accounts for 34 wt %.
6. The method for preparing a highly filled low modulus stretchable thermal interface material based on physical loose entanglement according to claim 1, characterized in that: In step 3, the catalyst is one or more of 1,8-diazabicyclo[5.4.0]undec-7-ene, triethylamine, tetramethylguanidine, hexahydropyridine, tetrahydropyridine, and triethylenediamine.
Citation Information
Patent Citations
Preparation method of rapid UV-cured fluorine-containing hydrophobic polyurethane elastic coating layer
CN104910344A
Preparation method of UV moisture dual-cured heat-conducting adhesive
CN112300746A
Heat-conducting gel and preparation method thereof
CN114292521A
High-thermal-conductivity polysiloxane composite material for regulating and controlling aluminum oxide in multiple sizes as well as preparation method and application of high-thermal-conductivity polysiloxane composite material
CN116396622A
Heat-conducting resin composition, heat-conducting fiber resin plate, preparation method of heat-conducting fiber resin plate and electronic equipment
CN118126491A